Estetika Musik Sufi Hazrat Inayat khan - Ubaidillah Anshari (Universitas Pahlawan Tuanku Tambusai, 2024)
This study was conducted to find out how music relates to man and his spirituality. The thoughts of Hazrat Inayat Khan indicate that music has an important role to play in spiritual attainment. Music is not just a means of entertainment or artistic expression, but also a means to stimulate spiritual awareness and connect the individual with the deeper dimensions of reality. By utilizing music as a means to spiritual attainment, one can gain greater depth of experience and experience meaningful transformation in their spiritual journey. This research utilized the (library research) method.